Genetic ancestry predicts male–female affiliation in a natural baboon hybrid zone. (October 2021) - Fogel, Arielle S.; McLean, Emily M.; Gordon, Jacob B.; Archie, Elizabeth A.; Tung, Jenny; Alberts, Susan C.
Abstract : Opposite-sex social relationships are important predictors of fitness in many animals, including several group-living mammals. Consequently, understanding sources of variance in the tendency to form opposite-sex relationships is important for understanding social evolution. Genetic contributions are of particular interest due to their importance in long-term evolutionary change, but little is known about genetic effects on male–female relationships in social mammals, especially outside of the mating context. Here, we investigate the effects of genetic ancestry on male–female affiliative behaviour in a hybrid zone between the yellow baboon, Papio cynocephalus, and the anubis baboon, Papio anubis, in a population in which male–female social bonds are known predictors of life span. We place our analysis within the context of other social and demographic predictors of affiliative behaviour in baboons. Genetic ancestry was the most consistent predictor of opposite-sex affiliative behaviour we observed, with the exception of strong effects of dominance rank. Our results show that increased anubis genetic ancestry is associated with a subtle, but significantly higher, probability of opposite-sex affiliative behaviour, in both males and females. Additionally, pairs of anubis-like males and anubis-like females were the most likely to socially affiliate, resulting in moderate assortativity in grooming and proximity behaviour as a function of genetic ancestry. Our findings indicate that opposite-sex affiliative behaviour partially diverged during baboon evolution to differentiate yellow and anubis baboons, despite overall similarities in their social structures and mating systems. Furthermore, they suggest that affiliative behaviour may simultaneously promote and constrain baboon admixture, through additive and assortative effects of ancestry, respectively. Highlights: Opposite-sex social relationships can have important fitness consequences. In hybrid baboons, genetic ancestry predicted male–female affiliative behaviour. Both an individual's genetic ancestry and that of its social partner mattered. Male–female affiliation was assortative with respect to genetic ancestry. Dominance rank and group demography also influenced male–female social affiliation.